The Influence of Internal and External Members Factors on The Sustainability of Cattle Farming in Jepara Regency, Central Java - Naroso, Naroso; Satmoko, Sriroso; Lestari, CM Sri (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
The purpose of research is finding out the influence of internal factors and external members on the sustainability of livestock fattening beef cattle breeding business in Central Java jepara regency.This research was conducted in February until Juni 2017 in Jepara regency. The used of research method is survey. The research material is breeder as respondent wit the total of 250 people who are taken fromtaken from 3 districts and villages stratified random sampling based on the number of cattle fire pieces in the most district, medium and at least.The equipment used here is a questionnaire (questionnaire). The data analysis used here is regression followed by path analysis.The independent variables in this research are internal factors and external factors of members. The internal factors of the members consist of: members motivation (X1), membersknowledge (X2), members attitude (X3) and external factors of members consisting of: information exposure (X4), the role of instructorrole (X5), livestock performance (X6). The dependent variable is member sustainability (Y1). The results showed that simultaneously and partially the members motivation, members knowledge, members attitude, the instructorrole and livestock performance affect significantly on the groupssustainability variable.